2021
DOI: 10.3389/fpls.2021.640163
|View full text |Cite
|
Sign up to set email alerts
|

A 598-bp InDel Variation in the Promoter Region of Bna.SOC1.A05 Is Predominantly Present in Winter Type Rapeseeds

Abstract: During rapeseed domestication and breeding, genetic diversity allowed to adapt it to different eco-geographical regions and to shape its useful traits. Structural variations (SVs), including presence/absence variations (PAVs), are thought to play a major role in the genetic diversity and phenotypic plasticity of rapeseed. In this study, we detected a 598-bp PAV within the promoter region of an Arabidopsis ortholog of a major flowering time gene and a downstream target of FLC, SOC1, which is one of the first ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…9 ). This supports other studies which have found SOC1 homologues in Brassica species to have different expression patterns, due to a partitioning of transcription factor binding sites between the different copies 48 , 86 , 87 . There are also between-variety differences between the copies, with the genes being consistently higher expressed in Westar relative to Tapidor (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9 ). This supports other studies which have found SOC1 homologues in Brassica species to have different expression patterns, due to a partitioning of transcription factor binding sites between the different copies 48 , 86 , 87 . There are also between-variety differences between the copies, with the genes being consistently higher expressed in Westar relative to Tapidor (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the BnaFT.A2 gene is strongly associated with flowering time differences between two winter OSR varieties 44 . Within other flowering time integrators, a specific promoter variant of BnaSOC1.A5 is predominantly found in winter OSR varieties 48 . These findings point towards variation in known flowering time genes from Arabidopsis being responsible for flowering time diversity between OSR, particularly in terms of vernalisation requirement.…”
Section: Introductionmentioning
confidence: 99%
“…First, mining InDel loci of different lengths has traditionally relied on the examination of a single reference genome, which leads to genomic bias and the inevitable loss of some InDel loci. Furthermore, these mining strategies based on single reference genomes often use second-generation short reads for mapping, but many important InDels associated with agronomic traits are too large to be easily detected with Illumina short reads (Liu et al, 2020;Matar and Melzer, 2021). Therefore, the identification of medium (3-50 bp) and large (≥50 bp) InDels requires the use of a multigenome collinearity approach rather than a single-genome mining strategy.…”
Section: Introductionmentioning
confidence: 99%